Anthropology of religion : the basics - James Bielo S (The basics, 2015)
"Anthropology of Religion: The Basics is an accessible and engaging introductory text organized around key issues that all anthropologists of religion face. This book uses a wide range of historical and ethnographic examples to address not only what is studied by anthropologists of religion, but how such studies are approached. It addresses questions such as:How do human agents interact with gods and spirits?What is the nature of doing religious ethnography? Can the immaterial be embodied in the body, language and material objects?What is the role of ritual, time, and place in religion?Why is charisma important for religious movements? How do global processes interact with religions?With international case studies from a range of religious traditions, suggestions for further reading, and inventive reflection boxes, Anthropology of Religion: The Basics is an essential read for students approaching the subject for the first time"--